O sacrificio enquanto arquétipo em "Ao Farol", a partir do mito de ifigênia - Silva, Mariana Soletti da (2022)
The present work aims to understand the presence of the archetype of the immolated woman in Ao farol, by Virginia Woolf, from the updating of the representation of sacrifice in the most remarkable representations of Iphigenia in theatre. The symbolism of sacrifice bears many similarities: the presence of mothers and daughters in the mythical narrative and in the Woolf novel, as well as the presence of social instability caused by the Trojan War and the transition from the Victorian Era to the First World War. Based on these assumptions, one hopes to strengthen the relationship between literature and psychoanalysis. The authors Bayard (2004), Durand (1993, 1996, 1997), Freud (2011, 2018), and Frye (1973) were used, as well as Jabouille et al. (1993), Jung (1978, 1991, 2000, 2001, 2014), Leader (1996), Mielitinsky (1987), Monfradini (2004), Reis (2013) and Ruthven (2010). When talking about the archetypes and their maternal types, Jung (2014) does not find sacrifice in the maternal aspect hypertrophy archetype, because, according to the author, women did not have an “self” to sacrifice. This dissertation intends to requalify this concept of archetype. The intention is not to create a new archetype but update it regarding feminist currents that would explain how, in fact, the "self" of women embedded in this archetype is asleep by social phenomena, such as the imposition of motherhood and the demand for paid domestic work, and the myth of Iphigenia itself, as the one who sacrifices herself for the greater good (men) amid social chaos. Lily Briscoe, however, is one of the women who reject the victimised woman archetype as a defense against the mother, as Jung (2014) would say. It is hoped that this text will help unearth the myth as a useful tool in unraveling the countless attempts at female conditioning to a life of perennial submission. To reach our results, the following authors were applied: Badinter (1980, 2011), Beauvoir (2008), Federici (2019), Friedan (1984), Frye (1973), Golden (2016, 2010), Jabouille et al. (1993), Jung (2001, 2014), Hooks (2018), Kehl (2009), Macfarlane (1990), Meruane (2018), Rank (2013), Pinho (2015), Sitta (2021), Stevens (2005), Woolger and Woolger (2007) and Woolf (2013, 2014, 2019).